2020
DOI: 10.1002/hep.31281
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Best Practice Advice for Hepatology and Liver Transplant Providers During the COVID‐19 Pandemic: AASLD Expert Panel Consensus Statement

Abstract: Background and Aims Coronavirus disease 2019 (COVID‐19), the illness caused by the SARS‐CoV‐2 virus, is rapidly spreading throughout the world. Hospitals and healthcare providers are preparing for the anticipated surge in critically ill patients, but few are wholly equipped to manage this new disease. The goals of this document are to provide data on what is currently known about COVID‐19, and how it may impact hepatologists and liver transplant providers and their patients. Our aim is to provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
674
0
20

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 409 publications
(705 citation statements)
references
References 48 publications
11
674
0
20
Order By: Relevance
“…Previous studies have shown that SARS‐CoV‐2 may aggravate liver injury in patients with viral hepatitis. ( 22,23 ) Therefore, liver injury in patients with chronic liver disease needs to be investigated and monitored.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that SARS‐CoV‐2 may aggravate liver injury in patients with viral hepatitis. ( 22,23 ) Therefore, liver injury in patients with chronic liver disease needs to be investigated and monitored.…”
Section: Discussionmentioning
confidence: 99%
“…(8) Given the high incidence of abnormal liver biochemistries in our cohort, we agree with the guidance from the American Association for the Study of Liver Diseases (AASLD) that liver biochemistries should be monitored in all hospitalized patients with COVID-19. (21) Viral hepatitis classically leads to an ALT-predominant hepatocellular injury; however, patients with COVID-19 did not match that pattern. Given that AST is also produced in muscle and patients with COVID-19 develop elevated markers of muscle injury, the AASLD and others have recommended consideration of myositis or cardiac injury as contributors to the AST elevation.…”
Section: Accepted Articlementioning
confidence: 99%
“…There are still no data on decompensated cirrhosis, patients on the transplantation DOI: 10.1159/000508116 list and, patients in the immediate posttransplant period or with rejection. Decisions about transplantation should be considered on a case-by-case basis at this stage of the pandemic [28].…”
Section: The Impact Of Preexisting Liver Disease On Covid-19mentioning
confidence: 99%
“…Liver biopsy should be deferred when not essential. Follow-up of liver patients will be increased when collaboration with primary care doctors is possible [28,29].…”
Section: Health Services and Facilitiesmentioning
confidence: 99%